FEM Analysis of Active Reduction of Torsional Vibrations of Clamped-Free Beam by Piezoelectric Elements for Separated Modes - AUGUSTYN, Elżbieta; KOZIEŃ, Marek S.; PRĄCIK, Michał (Archives of Acoustics, 2014)
Beams with rectangular cross-section, with large length-to-width ratio, can be excited to torsional vibrations. If the piezoelectric elements are mounted to the beam in pairs at the same cross-section with two separated elements positioned on the same side of the beam, and the voltages applied to them are in the opposite phase, they produce twisting moments which can be applied to reduce the torsional vibrations. Results of FEM simulations are presented and analysed in the paper. All analyses are performed for a steel free-clamped beam. The piezoelectric elements made of PZT material are mounted in pairs on one side of the beam. The analyses are done for separated natural modes.